2003
DOI: 10.1109/tns.2003.822092
|View full text |Cite
|
Sign up to set email alerts
|

Grazing angle proton scattering: effects on Chandra and XMM-Newton X-ray telescopes

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for. reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The Firsov scattering process in Geant4 has enabled us to address concerns raised in [4] with regard to a probable under-prediction of damaging proton fluences at the focal plane of the XMMNewton and Chandra telescopes. We have revised the XMMNewton simulation to include this new process for the relevant ranges of incident angle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Firsov scattering process in Geant4 has enabled us to address concerns raised in [4] with regard to a probable under-prediction of damaging proton fluences at the focal plane of the XMMNewton and Chandra telescopes. We have revised the XMMNewton simulation to include this new process for the relevant ranges of incident angle.…”
Section: Discussionmentioning
confidence: 99%
“…The most sensitive region of the CCD, i.e., the buried channel is at a silicon equivalent depth of m to the incident protons, i.e., it is behind the optical filter and the top layers of the CCD for the front illuminated case. The range of 100 keV protons in silicon is in the order of 0.92 m [3], [4], thus only incident protons with energy above 100 keV can reach the sensitive region of the CCD and cause damage. The fact that the incident proton spectrum is very steep [3]- [5], implies that the majority of the damaging protons are of energy just above keV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [1] [2][3] [4] have shown how low energy protons can reach the focal plane of Xray space telescopes by grazing angle scattering through the optics elements. As a consequence, imaging and spectrographic detectors can experience a deterioration of their performances, for example with a decrease of charge transfer efficiency (CTE) induced by non-ionizing energy loss (NIEL).…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of the radiation environment study, Monte Carlo simulations [2]- [4] with MCNPX [5] and Geant4 [6] and the study of physics models [7] for Chandra and XMM-Newton observatories were carried out, and succeeded in explaining the degradation as being due to damage by background protons propagating through the X-ray telescope optics by grazing incidence scattering processes. These studies supplied significant information about the on-orbit radiation background that was not known before the accident because Chandra and XMM-Newton have atypical orbits for X-ray observation satellites.…”
Section: Introductionmentioning
confidence: 99%